Rights of Gross Human Rights Violation Victims (International and National Law Perspective) - Abdul Haris Samendawai (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Rights of gross human rights violation victims have been much regulated in a number of constitutional regulations. However, conceptual shortfalls in substantial formulations are still present in the positive law. The substantial aspect shortfalls have the potential to have detrimental implication to the protection of gross human right violation victim’s rights considering the procedural aspects will refer to the material law. This condition certainly become a challenge which is expected to motivate all related parties to improve and bring their best contribution in the effort to protect, improve human rights, and enforce law and justice to the victim.Keywords : Rights of Victim, The Serious Violence Against Human Rights, International Law